Quality control of some etoricoxib products available in syrian market - قدّار نسرين; بركات هلا; سلامي بشرى (Latakia University Journal -Medical Sciences Series, 2021)
Etoricoxib is a highly selective cyclooxygenage-2 (COX-2) inhibitor. administered orally as an analgesic drug,indicated in the symptomatic relief of osteoarthritis rheumatoid arthritis and the pain and sings of inflammation associated with acute gouty arthritis. It belongs to class II under BCS (Biopharmaceutics Classification System). Study’s aim was to evaluate three generic Etoricoxib 120mg tablets from different companies to assess their bioequivalence in vitro. And to ensure that etoricoxib is eligible for biowaiver by performing saturation test. General quality assessments of these tablets like weight variation, content uniformity, hardness, and disintegration time were carried out Compared to the reference drug ARCOXIA. All tablets achieved both weight uniformity, Content uniformity. B3 batch did not meet the assay test. As for the dissolution test, Dissolution profiles were compared using dissimilarity factor (f1) and similarity factor (f2).The results showed that there was no bioequivalence between local companies and brand. Etoricoxib eligible for biowaiver, because it remains in a supersaturated state without precipitation when transferred from simulated gastric fluids (SGF) into simulated intestinal fluids (SIF).